Estimating the market effect of a trade war: The case of soybean tariffs. (December 2021) - Adjemian, Michael K.; Smith, Aaron; He, Wendi
Highlights: In 2018, China levied a 25% retaliatory tariff on U.S. soybean exports. That tariff led Chinese buyers to favor Brazilian soybeans. We estimate the tariff lowered U.S. prices at the Gulf by $0.74/bu on average for about five months. USDA's trade aid payments for soybean damages summed to $3.70 for 2 bushels over two years. We project that USDA's trade aid to soybean producers exceeded the tariff damage by about $5.4 billion. Abstract: In 2018, China retaliated to U.S. trade actions by levying a 25% retaliatory tariff on U.S. soybean exports. That tariff shifted market preferences so that Chinese buyers—who make up a substantial share of total world consumption—favored Brazilian soybeans. We use the relative price of a substitute (RPS) method to estimate that the resulting trade disruption effectively drove a wedge into the world soybean market, lowering U.S. prices at Gulf export locations by $0.74/bu on average for about five months, and increasing Brazilian prices by about $0.97/bu, compared to what would have been observed without the tariff in place. By the end of that period, world markets adjusted and the soybean prices in both countries returned to the ex-ante state of near parity, even if U.S. export volume did not recover until the end of the following marketing year. Our price impact estimate is substantially lower than subsequent U.S. government "trade aid" payments to American soybean producers: although actual payments to producers varied based on county-level differences, USDA's nominal calculation of the commodity-specific payment rate for soybeans under MFP summed to $3.70 for two bushels produced over the course of two years. We project that USDA's near-$8.5 billion in trade aid to U.S. soybean producers exceeded the tariff damage by about $5.4 billion. These difference could be attributed to USDA's broader definition of "economic injury", beyond the short-run price impacts we estimate.